Social Impact Waqf: Integrating Islamic Philanthropy with Halal Entrepreneurship Ecosystem - Harjoni Desky; Della Octavia Indana (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2026)
This article explores the integration of social impact waqf into the halal entrepreneurship ecosystem as a model for inclusive and sustainable Islamic economic empowerment. Using a qualitative and conceptual approach, the study reviews relevant literature, policy frameworks, and best practices to understand how productive waqf can support value-based halal businesses. Findings indicate that when managed professionally, waqf has the potential to act as Islamic venture capital—providing not only funding but also infrastructure, training, and capacity building for halalpreneurs. In Indonesia and Malaysia, several initiatives have successfully linked waqf funds with halal business incubators, community cooperatives, and agricultural enterprises, demonstrating its practical viability. However, challenges persist, such as low public literacy, limited digital integration, and the lack of synergy between waqf institutions, government agencies, and the halal industry. The paper concludes that aligning Islamic philanthropy with entrepreneurship serves both spiritual and socio-economic goals. It enhances financial inclusion, reduces poverty, and strengthens Muslim middle-class resilience, while also contributing to the achievement of SDGs. Therefore, a structured, transparent, and digitally-enabled waqf model is recommended to build trust and maximize impact. This study offers a new paradigm for Islamic economic development—where religious values and modern business strategies converge to produce ethical, community-based growth.